Pengaruh Strategi Pembelajaran Active Knowledge Sharing (AKS) Terhadap Kemampuan Komunikasi dan Hasil Belajar IPA Siswa Sekolah Dasar - Arista, Ai; Yanto, Ari; Febriyanto, Budi (Papanda Publisher, 2025)
The types of research analyzed and reviewed in this study are quantitative research, and classroom action research. The data collection technique in this literature study research uses the documentation method. This study aims to describe the results of the analysis and study of the Effect of Active Knowledge Sharing (AKS) Learning Strategy on Communication Skills and Learning Outcomes of Elementary School Students. Based on the results of this literature study research, it can be concluded that the use of the Active Knowledge Sharing (AKS) Learning Strategy on Communication Skills and student learning outcomes can provide a positive response from students in the form of increasing student activeness both physically and psychologically which in turn can improve student learning outcomes or the Active Knowledge Sharing (AKS) Learning Strategy has an effect on Communication Skills and student learning outcomes. This can be proven from various kinds of trial results on the use of Active Knowledge Sharing (AKS) Learning strategies carried out at the elementary school level through various types of research. Both quantitative research. This shows that the use of the Active Knowledge Sharing (AKS) Learning Strategy which has the characteristics of active students in learning activities ultimately affects student learning outcomes because this strategy can create an active student learning atmosphere and can improve learning achievement. For example, by making a study schedule and carried out with discipline, reading or taking notes, and concentration.